Research on the Mechanism and Material Basis of Corn (Zea mays L.) Waste Regulating Dyslipidemia - Xiaodong Wang; Lewei Cao; Jiajun Tang; Jiagang Deng; Erwei Hao; Gang Bai; Pei Ling Tang; Jieyi Yang; Huaying Li; Lihao Yao; Cuiwei He; Xiaotao Hou (MDPI AG, 2024)
Corn (Zea mays L.) is an essential gramineous food crop. Traditionally, corn wastes have primarily been used in feed, harmless processing, and industrial applications. Except for corn silk, these wastes have had limited medicinal uses. However, in recent years, scholars have increasingly studied the medicinal value of corn wastes, including corn silk, bracts, husks, stalks, leaves, and cobs. Hyperlipidemia, characterized by abnormal lipid and/or lipoprotein levels in the blood, is the most common form of dyslipidemia today. It is a significant risk factor for atherosclerosis and can lead to cardiovascular and cerebrovascular diseases if severe. According to the authors' literature survey, corn wastes play a promising role in regulating glucose and lipid metabolism. This article reviews the mechanisms and material basis of six different corn wastes in regulating dyslipidemia, aiming to provide a foundation for the research and development of these substances.